2019
DOI: 10.3126/jonmc.v8i2.26714
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Information Education and Communication on Menstrual Hygiene among Adolescent School Girls of Jumla District

Abstract: Background: Menstruation and menstrual practices are darkened by taboos and different societal as well as cultural restrictions, which results in lack of adequate knowledge in adolescents regarding the scientific facts of menstruation as well as healthy menstrual hygiene practices. The objective of the study was to find out the effectiveness of information, education and communication (IEC) on menstrual hygiene among adolescents of Jumla district. Materials and Methods: Quasi-experimental research design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…It corroborates the fact that education on menstruation hygiene to the secondary school adolescent girls is one of the effective strategies to enhance the level of knowledge on menstrual hygiene. These results are similar to the results of a study conducted in Southern Haryana, India [22], Riyan City Saudi [31], Damietta City, Egypt, [23] Jumla District, Nepal, [24] and in Pune city, India [25].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It corroborates the fact that education on menstruation hygiene to the secondary school adolescent girls is one of the effective strategies to enhance the level of knowledge on menstrual hygiene. These results are similar to the results of a study conducted in Southern Haryana, India [22], Riyan City Saudi [31], Damietta City, Egypt, [23] Jumla District, Nepal, [24] and in Pune city, India [25].…”
Section: Discussionsupporting
confidence: 90%
“…The health education was delivered by using PowerPoint presentations, pamphlets and a short video. The education package was formulated with adequate literature review [21][22][23][24][25] and also with the aid of the expert in the area of MHM. To ensure the reliability of the tool and the educational package, pretesting was done.…”
Section: Data Collection Tools and Techniquesmentioning
confidence: 99%
“…(z= 17.13 , p=<0.001) which explained that the education on menstruation hygiene to the secondary school girls is one of the good strategy to enhance level of knowledge on menstruation hygiene. This results are similar to the results of a study conducted in Southern Haryana, India, 32 Riyan City Saudi, 25 Damietta City, Egypt, 33 Jumla District , Nepal, 34 Pune city , India 35 This study identifies that large percentage of respondents experiencing restriction of cultural activities during menstruation .The most common limited activity was to attend and perform religious activities. Similar findings was observed in study conducted in West Bengal, India, 36 Chitwan Nepal, 30 Kathmandu Valley, Nepal.…”
Section: Discussionsupporting
confidence: 87%
“…The study by Dahal and Acharya revealed that 8.9% of the respondents had high knowledge during pretest which was significantly increased to 60.7% during posttest and 27.7% of the respondents had good practice during pretest which was significantly increased to 51.8% during posttest. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%